A Review: Damage Assessment of Reinforced Concrete Buildings Using Ambient Vibration Testing - Abd Rahman, Najihah; Kamarudin, Ahmad Fahmy (Recent Trends in Civil Engineering and Built Environment, 2024)
Ambient vibrations such as excitations from the environment, human activities and seismic events had cumulatively induce damages to RC building. Cost-consuming regular building maintenance was the reason for a building’s integrity to be assessed first before decision making. Recently, vibration-based damage assessment approach had been widely practiced using data from ambient vibration testing (AVT). The purpose of this study was to identify the damage assessments on structure using vibration approach and to investigate the empirical and analytical based damage relationships with scope of stiffness or natural frequency as the main parameters in damage assessments. From literature studies, ten related articles that utilized stiffness or natural frequency in their damage relationships had been collected and reviewed. Vulnerability index, damage index and rapid screening indicator were the damage relationships employed in the reviewed studies and the results had been discussed in terms of damage detection validation, damage parameter and damage state.  Stiffness was used as the main parameter in damage index and rapid screening indicator while natural frequencies was used in vulnerability index. Based on the review conducted, the application of stiffness or natural frequency in the damage relationships was reliable to detect damage with high accuracy. This study had suggested for future studies to investigate the method to convert the subsequent damage values into building’s damage condition since there is still no appropriate development on this damage rating score.